(untitled) - Öpik, Helgi (Cambridge, UK, 2005)
The Physiology of Flowering Plants is divided into two parts. Part one looks at nutrition and transport. The survey of plant physiology accordingly begins with photosynthesis and the products of photosynthesis. It details how a plant obtains and processes light and CO2 while further chapters consider how they acquire and transport water, and absorb minerals. Part two discusses physiology in growth and development. It examines plant growth hormones, and cell growth and differentiation. Vegetative development, photomorphogenesis, reproductive development, growth movements and reactions to environmental stresses are also considered.
Keywords: Plant physiology